Nanoparticles used in dentistry: A review - Subhashree Priyadarsini; Sumit Mukherjee; Monalisa Mishra (Elsevier, 2018)
Nanotechnology is widely used in our day to day life including its use in medicine. Using nanotechnology, it is easy to analyze and manipulate atoms, chemical bonds and molecules present between various compounds. Nanotechnology is used in the dental field as nano dentistry. While choosing the nanoparticle for the use in the field of nano dentistry its chemical, physical, along with the biological aspect of nanostructures are taken into account. Often various atoms or molecules are added to form the functional structure. Nanostructures are used in innovations or diagnosis of dentistry. Some nanoparticles are used for oral disease preventive drugs, prostheses and for teeth implantation. Nanomaterials further deliver oral fluid or drugs, preventing and curing some oral disease (oral cancer) and maintain oral health care up to a high extent. This review summarises the use of various widely used nanoparticle in the field of dentistry.